Changing in lifestyle of people in tourist destinations - Bùi, Thanh Thủy (2021)
Almost researchers, practical activists, managers in tourism have realized economic effects of tourism is the rooted reason to other effects and it create the changes in living standards, lifestyle through concept, behavior, attitude, communication of local people and tourist. It may be that the change in lifestyle of people on tourist destinations is the indirect economic effects of tourism to them. There effects can be effective or ineffective in difficult scales and need more deep researching papers.